The generic structure potential (GSP) of STI doctor-patient interactions in southwest Nigeria - Amusa, Oluwaseun (Revista do GEL, 2024)
This study describes the generic structure potential (GSP) of sexually transmitted infection (STI) consultations in Nigeria. It is a further effort from previous studies not only in its consideration of the phase structure of consultations in a specific medical context, but also in its exploration of both the broad and narrow generic structure potential of the consultations. Fifty audio recordings of mixed-visit doctor-patient interactions in hospitals in three states in southwest Nigeria constitute the data. The data were analysed using Halliday and Hasan’s (1985) Generic Structure Potential theory (GSP). The analysis revealed four broad stages in the structural organisation of STI medical interactions, namely Opening (O), Diagnostic Interactions (DI), Treatment Recommendations (TR), and Closing (C). The obligatory elements in the broad catalogue are the diagnostic interactions and treatment recommendations, while the narrow GSP of the phases revealed the doctor’s problem elicitation as the obligatory element in the opening phase, the patient’s problem presentation activity was solely obligatory in DI, and the doctor’s treatment procedure, the only mandatory activity of the TP phase. The study concludes that the diagnostic interaction and treatment recommendation phases define medical consultations in STI (and HIV) encounters in Nigeria.